Analysis of the Influence of Academic Service Quality on Improving Student Satisfaction Using the SERVQUAL Method - Maringan Sianturi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In the context of increasing competition among higher education institutions, maintaining high-quality academic services has become essential to ensure student satisfaction. This study aims to analyze the influence of academic service quality on student satisfaction using the SERVQUAL method, which comprises five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A total of 150 students from three academic programs participated as respondents. Data were collected through questionnaires measuring students’ expectations and perceptions of academic services and were analyzed using the gap score (P–E) for each indicator. The findings show that the assurance dimension has the highest positive gap value, indicating that staff competence, politeness, and professionalism exceed student expectations. The tangibles and empathy dimensions also demonstrate relatively favorable performance. In contrast, the responsiveness and reliability dimensions exhibit negative gaps, suggesting that response speed, staff attentiveness, and service consistency still require improvement. Academic service quality is categorized as adequate but necessitates enhancements in responsiveness and reliability to increase student satisfaction. This study contributes to the evaluation of service quality in higher education and serves as a reference for decision-making in improving academic service performance.